The role of sensory innervation in homeostatic and injury-induced corneal epithelial renewal - Feinberg, Konstantin; Tajdaran, Kiana; Mirmoeini, Kaveh; Däschler, Simeon C.; Henriquez, Mario A.; Stevens, Katelyn E.; Mulenga, Chilando M.; Hussain, Arif; Hamrah, Pedram; Ali, Asim; Gordon, Tessa; Borschel, Gregory H. (International journal of molecular sciences, 2023)
The cornea is the window through which we see the world. Corneal clarity is required for vision, and blindness occurs when the cornea becomes opaque. The cornea is covered by unique transparent epithelial cells that serve as an outermost cellular barrier bordering between the cornea and the external environment. Corneal sensory nerves protect the cornea from injury by triggering tearing and blink reflexes, and are also thought to regulate corneal epithelial renewal via unknown mechanism(s). When protective corneal sensory innervation is absent due to infection, trauma, intracranial tumors, surgery, or congenital causes, permanent blindness results from repetitive epithelial microtraumas and failure to heal. The condition is termed neurotrophic keratopathy (NK), with an incidence of 5:10,000 people worldwide. In this report, we review the currently available therapeutic solutions for NK and discuss the progress in our understanding of how the sensory nerves induce corneal epithelial renewal.